Determinants of catering performance of women entreprenuers - Angeles, Arlene A. (2004)
This study determined if women-caterers; personality characteristics, work motives, and business practices are related to organizational performance. These independent variables dominant in women-entrepreneurs were determined using factor analysis through principal component method. Descriptive design was employed in this study and utilized quantitative as well as qualitative approaches to research. Respondents were 108 women-caterers of key cities in Metro Manila. A snowball type of sampling was undertaken to come up with an ideal number of respondents. A questionnaire was distributed to the respondents and quantitative data were analyzed using means and standard deviations; frequency and percentages. The researcher analyzed for case studies to augment the results of the quantitative data. Results revealed that except for work organization and future orientation, there is no relationship between personality characteristics and organizational performance. Conversely, work motives and business practices are related to firms' performance. Analysis of cases revealed that additional problems encountered were the difficulty of handling employees ab, purchasing of raw materials and the increase in the number of competitors. Based on the findings, the researcher recommends the following: 1) part of the competencies that should be developed in a school curriculum is the student's energy, work organization, and future orientation objectives; 2) entrepreneurs must be clear about their profit objectives, as viability of a business depends on the income generated by the firm; 3) financial management subjects should be prioritized for those who want to become entrepreneurs; 4) attendance to trainings, seminars, workshops, informal and formal schooling is necessary to enhance one's entrepreneurial skills; 5) lack of marketing knowledge should be addressed; 6) future entrepreneurs must have a vision for their company; and 7) TESDA initiated policies may be used by researchers and policy makers for the creation of future reforms on this. Future users of the study may make use of the 1) snowball sampling technique to identify potential respondents in case of difficulty in gathering respondents; 2) longitudinal study to obtain a clearer picture of the relationship of the independent variables of this study with organizational performance; 3) inclusion of other type of respondents from different types of food service operations can be considered; 4) construction of a more refined questionnaire based on the findings of the interviews that will include other variables; and 5) regression analysis to capture important variables that contribute to organizational performance.